CHARACTER BUILDING EFFORTS AT MADRASAH ALIYAH NURUL HUDA PAOWAN PANARUKAN SITUBONDO - MUSADDAD , AHMAD MUSADDAD (Tsaqofah : Jurnal Pendidikan Islam, 2021)
This research was conducted to describe the efforts of Madrasah Aliyah Nurul Huda Paowan Panarukan Situbondo in implementing education to shape the character of students in absorbing and applying religious values that prioritize faith, where faith becomes the main focus as a form of character building. This research uses descriptive qualitative methods, with data collection techniques of interviews, observations and documentation of all activities and efforts made by Madrasah Aliyah Nurul Huda in shaping the character of its students. This research was conducted during one semester to see a full portrait of student activities, the effectiveness of activities and the involvement of all teachers in shaping student character. The results of this study are that many of the efforts of Madrasah Aliyah Nurul Huda Paowan Panarukan Situbondo, have been maximized. All forms of activities are carried out consistently and fully supervised. All activities have references that are referred from several classic literacies in the era of Salafus Shalih. All forms of activity efforts emphasize religiosity by utilizing environmental support and pesantren infrastructure so that they have high effectiveness.